2015
DOI: 10.1016/j.jad.2015.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of people dying by suicide after job loss, financial difficulties and other economic stressors during a period of recession (2010–2011): A review of coroners׳ records

Abstract: Financial difficulties, little past psychiatric history, low levels of service contact and having financial dependents were more common in 'recession-related' deaths. This suggests that interventions to prevent recession-related rises in suicide should be focused on non-clinical agencies and initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(74 citation statements)
references
References 16 publications
4
60
1
3
Order By: Relevance
“…Recent research into suicides occurring during a period of recession indicated that those whose suicide appeared to be related to consequences of recession were largely still in work, cohabiting, with financial dependents but had no contact with secondary-care psychiatric and little recent contact with primary-care services (Coope et al 2015). This indicates the need for research into how best to ( a ) identify those at risk of adverse mental health outcomes during recession, and ( b ) intervene to reduce risk among those not in contact with services.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research into suicides occurring during a period of recession indicated that those whose suicide appeared to be related to consequences of recession were largely still in work, cohabiting, with financial dependents but had no contact with secondary-care psychiatric and little recent contact with primary-care services (Coope et al 2015). This indicates the need for research into how best to ( a ) identify those at risk of adverse mental health outcomes during recession, and ( b ) intervene to reduce risk among those not in contact with services.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two studies examined psychological autopsy data for individuals with likely gambling disorder and who died from suicide, and both studies found a link between gambling‐related financial problems and suicide . Finally, research outside of the gambling field has consistently demonstrated that financial stress is a significant risk factor for dying from suicide …”
Section: Background and Objectivesmentioning
confidence: 99%
“…Issues related to finance and employment 'contributed substantially' to 13% of suicides and were 'the key contributing factor' to 4%. 5 Clearly, suicide rates barely scratch the surface of the mental illness caused or triggered by the recession. Yet only 25% of people with depression or anxiety access help.…”
Section: Care In the Community In Crisis Mark Greener Bsc (Hons) Msbmentioning
confidence: 99%